2004
DOI: 10.1002/cne.20430
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and cytoarchitecture of the ventral telencephalon in the salamander Plethodon shermani

Abstract: The cytoarchitecture and axonal connection pattern of centers in the ventral telencephalon of the salamander Plethodon shermani were studied using biocytin for anterograde and retrograde labeling of cell groups, as well as by intracellular injections. Application of biocytin to the main and accessory olfactory bulbs identified the olfactory pallial regions and the vomeronasal portion of the amygdala, respectively. According to our results, the amygdala of Plethodon is divided into (1) a rostral part projecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 59 publications
5
41
0
Order By: Relevance
“…In the (anuran) amphibian brain, a central extended amygdala is thought to remain undivided, representing an ancestral condition [Roth et al, 2004]. Evidence suggests that the central extended amygdala of the urodele amphibian brain (Plethodon shermani) , including the lateral portion of the bed nucleus of the stria terminalis, is functionally equivalent to that of mammals [Laberge and Roth, 2005]. In mammals, the bed nucleus of the stria terminalis receives projections from the basolateral amygdala and in turn, projects to hypothalamic and brainstem target areas that mediate many autonomic and behavioral responses to adverse stimuli and participates in behavioral responses to anxiety and stress, possibly slower-onset, long-lasting responses that accompany sustained threats [Walker et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…In the (anuran) amphibian brain, a central extended amygdala is thought to remain undivided, representing an ancestral condition [Roth et al, 2004]. Evidence suggests that the central extended amygdala of the urodele amphibian brain (Plethodon shermani) , including the lateral portion of the bed nucleus of the stria terminalis, is functionally equivalent to that of mammals [Laberge and Roth, 2005]. In mammals, the bed nucleus of the stria terminalis receives projections from the basolateral amygdala and in turn, projects to hypothalamic and brainstem target areas that mediate many autonomic and behavioral responses to adverse stimuli and participates in behavioral responses to anxiety and stress, possibly slower-onset, long-lasting responses that accompany sustained threats [Walker et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in retention times strongly suggested identical structures between native and recombinant PMF-G. (B) Far UV CD analysis of native and recombinant PMF-G produced very similar spectra, with estimated secondary structure of ~11% α-helix and ~29% β-sheet content (K2D3; 27), which is similar to NMR results measured by DSS in Pymol (11% α-helix, 33% β-sheet) [72,73]. (C) Both PMF-G and rPMF-G were treated with TCEP for 20min and major peaks represent 4, 3, 2, 1, and 0 intact disulfides.…”
Section: Figure 13 Comparison Of Native and Recombinant Pmf-gsupporting
confidence: 64%
“…In the species Plethodon shermani, during a courtship behavior known as tail-straddling walk, male salamanders will privately deliver pheromones to a female by "slapping" a large pad-like gland on his chin (the mental gland) to the female's nares [85]. Pheromones diffuse into the female nasal cavity, bind to receptors on neurons in the vomeronasal organ, activate regions of the brain involved in pheromone response, and regulate female mating behavior [70,73,83,86,92]. Chemical analysis of the pheromone extract revealed two major components: Plethodontid Receptivity Factor (PRF) and Plethodontid Modulating Factor (PMF).…”
Section: Agb Uptake Assay and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, considerable studies on telencephalon of the vertebrates have been reported. These investigations include research on fish, such as Sinipeca chuatsi [1] , Schizothorax prenant [2] , and Onchorhynchus keta [3] ; the histological studies on the telencephalon of tailed amphibians, such as Onychodactylus fischeri [4] , the Chinese giant salamander [5] , and Batrachuperus tibetanus [6] ; the correlative mode between cytoarchitecture of the ventral telencephalon and the axons in Plethodon shermani [7] ; the telencephalic efferents of tiger salamander [8] ; the olfactory bulb, accessory olfactory bulb and cerebral hemisphere of Anuran amphibian [9,10] ; the olfactory bulbs, olfactory tract and central nervous telencephalon of the reptiles, such as new-Hatching Allgator sinensis [11][12][13][14] ; and the Golgi-Cox of anterior dorsal ventricular and the rostrolateral area of anterior dorsal ventricular (ADVR) of telencephen in Gekko gecko [15,16] . However, few studies have been reported on the developmental process of the central nervous system, except on that of trituberculatus [17] , goats [18] , and Xenopus [19,20] .…”
Section: Introductionmentioning
confidence: 99%